Microstrip Hybrid Coupler with a Wide Stop-Band Using Symmetric Structure for Wireless Applications - A. Rezaei; L. Noori (Journal of Microwaves, Optoelectronics and Electromagnetic Applications)
Abstract In this paper, a wide stop-band microstrip coupler is presented. The proposed structure consists of coupled lines and step impedance cells, which are integrated to operate at 2.82 GHz for wireless applications. This coupler is formed by a symmetric structure so that the locations of the output ports relative to input are quite similar. Accordingly, the magnitudes (also phases) of S21 and S31 overlap each other so that input signal can be selected through the output ports equally. There are little differences between the magnitudes and phases of S21 and S31 so that 0.97° phase shift is obtained. In comparison with previous works, the performance of the introduced coupler is improved. To get a better isolation, return loss and harmonic attenuation the frequency response is optimized without significant increase in circuit size. Moreover, the first, second and third harmonics of S21 and S31 are well attenuated as well as a wide stop-band is obtained up to 15.1 GHz. The realized coupler is fabricated and measured. There is a good agreement between simulated and measured results, which confirms the design process.